Anthropology and alterity: responding to the other - Leistle, Bernhard (Routledge studies in anthropology, 2017)
Alterity or otherness is a central notion in cultural anthropology and philosophy, as well as in other disciplines. While anthropology, with its aim of understanding cultural difference, tends to take otherness as a fact, there have been vigorous attempts in contemporary philosophy, particularly in phenomenology, to answer the fundamental question: What is the Other? This book brings the two approaches to otherness - the hermeneutical pragmatics of anthropology, and the radical reflection of philosophy - together, with the goal of enriching one through the other. The philosophy of the German phenomenologist Bernhard Waldenfels, up to now little known to anthropologists, has a central position in this undertaking. Waldenfels's concept of a responsivity to the Other offers to cultural anthropology the possibility of a philosophical engagement with the Other that does not contradict the project of making sense of concrete empirical others. The book illustrates the fertility of this new approach to alterity through a broad spectrum of themes, ranging from reflections on theory formation, via discussions of race and human-animal relations, to personal meditations on experiences of alterity
Literaturangaben
Keywords: Aufsatzsammlung; Waldenfels, Bernhard; Ethnologie; Das Andere